2014
DOI: 10.4162/nrp.2014.8.6.688
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of vitamin B6intake and status of 20- to 64-year-old Koreans

Abstract: BACKGROUND/OBJECTIVESRecent research regarding vitamin B6 status including biochemical index is limited. Thus, this study estimated intakes and major food sources of vitamin B6; determined plasma pyridoxal 5'-phosphate (PLP); and assessed vitamin B6 status of Korean adults.MATERIALS/METHODSThree consecutive 24-h diet recalls and fasting blood samples were collected from healthy 20- to 64-year-old adults (n = 254) living in the Seoul metropolitan area, cities of Kwangju and Gumi, Korea. Vitamin B6 intake and pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…In raw foods, nutrient contents are changed by food preparation, cooking conditions (e.g., time and temperature), and the addition of different ingredients depending on household preferences. Therefore, riboflavin cooked foods consumed by the subjects might be underestimated [ 37 ]. Three consecutive 24-h recalls were obtained from each subject, which may not be captured as usual intake.…”
Section: Discussionmentioning
confidence: 99%
“…In raw foods, nutrient contents are changed by food preparation, cooking conditions (e.g., time and temperature), and the addition of different ingredients depending on household preferences. Therefore, riboflavin cooked foods consumed by the subjects might be underestimated [ 37 ]. Three consecutive 24-h recalls were obtained from each subject, which may not be captured as usual intake.…”
Section: Discussionmentioning
confidence: 99%
“…The most biologically active form of vitamin B 6 is pyridoxal 5'-phosphate, which is a cofactor for transaminases, decarboxylase, racemases, and other enzymes used in the metabolic transformations of amino acids and nitrogencontaining compounds (167). Vitamin B 6 is widely distributed in foods from plant and animal origin.…”
Section: Vitamin Bmentioning
confidence: 99%
“…Vitamin B 6 deficiency is a concern in high-income as well as low-income countries. A nationally representative survey found that one-third of South Koreans have marginal or deficient status (Kim & Cho, 2014). It is estimated that approximately 10% to 20% of the U.S. population is at risk for deficiency (Pfeiffer et al, 2013), and 5% to 35% of U.S. adults have PLP below the deficiency cutoff of 20 nmol/L (Bird, Murphy, Ciappio, & McBurney, 2017;Morris, Picciano, Jacques, & Selhub, 2008).…”
Section: Pyridoxine (Vitamin B 6 )mentioning
confidence: 99%